(untitled) (Al-Academy, 2017)
dance that reflect deferent sides from life human , in this search ensure for the causation can the expressionistic dancing be development acting actor in Iraqis theatre ? so this search concept of section one composed of the search problem , and important the search and need it , aimed the search , lines search it composed of the lines time , place , and lines subject , and the searcher ended this section with practical terms . Section tow – theatrical lines form that composed of part one the dance kinds: the expressionistic dancing, is very important in analyses the symbol . part tow the important of the dance in the acting. Section three concept of analyses the servers play section four concept of search results , and end the search for important sources and the abstract